STUDY OF ADAPTATION AND ECONOMICALLY USEFUL FEATURES OF «HANHYAP» CHICKEN SPECIES FOR THEIR EMPLOYMENT AT PRIVATE COMPOUNDS AND FARMS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article present the research outcomes of «Hanhyap» chicken species. TheBiochemical indicators of chicken serum have been fixed and their adaptation was rated.
Keywords: chickens, poultry, adaptation, biochemistry, blood.